1987
DOI: 10.3177/jnsv.33.49
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol composition of winged bean (Psophocarpus tetragonolobus)

Abstract: SummaryWinged beans were extracted with hexane and the extracted lipid was analyzed by HPLC for its triacylglycerol (triglyceride) compo sition on a Lichrosorb RP-18 column with acetonitrile-tetrahydrofuran -dichloromethane (6:2:1) solvent mixtures. The chromatography yielded more than 21 peaks, and each triacylglycerol was analyzed for fatty acids by GLC. The major triacylglycerols were found to be behenoyl-linoleoyl oleoylglycerol (21.3%), trioleoylglycerol (10.5%) and behenoyl-diole oylglycerol (15.6%). Win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…This plausibly contributed to the highest cloud point of 9.7 °C observed with 75% WBSO addition as discussed earlier. The TAG composition of WBSO reported in this study were in agreement with those reported in earlier studies (Omachi et al, 1987;Makeri et al, 2016Makeri et al, , 2018.…”
Section: Triacylglycerols Compositionsupporting
confidence: 93%
“…This plausibly contributed to the highest cloud point of 9.7 °C observed with 75% WBSO addition as discussed earlier. The TAG composition of WBSO reported in this study were in agreement with those reported in earlier studies (Omachi et al, 1987;Makeri et al, 2016Makeri et al, , 2018.…”
Section: Triacylglycerols Compositionsupporting
confidence: 93%
“…The preparative TLC step prior to HPLC was eliminated. No difference in the TAG fractions separated by HPLC, with or without TLC pretreatment, was shown earlier in winged bean oil and coconut oil ( , ).
1 Sample HPLC Chromatogram of the triacylglycerol composition of the oils of different coconut cultivars and hybrids.
…”
Section: Resultsmentioning
confidence: 69%
“…The preparative TLC step prior to HPLC was eliminated. No difference in the TAG fractions separated by HPLC, with or without TLC pretreatment, was shown earlier in winged bean oil and coconut oil (13,15).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Thus, in terms of overall trends, our results agree well with other reports of pulse TAG compositions. Omachi et al (1987) performed analysis of winged bean (Psophocarpus tetragonolobus) TAGs by F I G U R E 6 Hierarchical cluster analysis (HCA) using correlation of the molecular species compositions of triacylglycerols of pulses. Number of clusters set at 3 from principal component analysis.…”
Section: Tag Percent Relative Quantificationmentioning
confidence: 99%